The use of botulinum toxin in pregnant and lactating women: literature review (Research, Society and Development, 2020)
It’s perceived that currently the search for professionals who perform facial harmonization is growing more and more, and consequently the use of botulinum toxin as well, which is leading to a very present theme in studies and research among dentists, but a factor interesting that we realize is that there is a shortage in production in its use in pregnant women and from this we decided to carry out a research that aims to evaluate the studies in relation to the use of botulinum toxin in pregnant women and lactating women, for this we decided to do a literature review , where among the articles found, 30 articles were used that had a more relevant character for the production of this research, which made us realize that due to the botulinum toxin being one of the most used materials, it is necessary that there is a greater collection of academic productions in its application in pregnant and lactating women, in order to avoid possible damage to the mother and fetus.